2010
DOI: 10.1080/14786410903370908
|View full text |Cite
|
Sign up to set email alerts
|

Propolis inhibits the proliferation of human leukaemia HL-60 cells by inducing apoptosis through the mitochondrial pathway

Abstract: Propolis, a natural product derived from plant resins collected by honeybees, has been reported to exert a wide spectrum of biological functions. This research aimed at investigating the effect of propolis on the proliferation of human leukaemia HL-60 cells and whether propolis might induce apoptosis in HL-60 cells. The results showed dose- and time-dependent decreases in the proliferation of HL-60 cells treated with propolis (above 3 microg mL(-1) of propolis). Further studies revealed that the anti-prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
11
0
2
Order By: Relevance
“…Additionally, the above observation is in line with results of a study in which propolis induced apoptosis through the release of cytochrome c from mitochondria to the cytosol and through activating caspase-3 in human leukemia HL-60 cells in a concentration-dependent manner (3-50 μg/ml for cytochrome c and 10-50 μg/ml for caspase-3) [34]. The cell death induced by propolis was largely prevented by treating HL -60 cells with 30 μM z-DEVD-fmk, a caspase-3 inhibitor [23].…”
Section: The Effect Of Propolis On the Apoptotic Process In Cancer Cellssupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, the above observation is in line with results of a study in which propolis induced apoptosis through the release of cytochrome c from mitochondria to the cytosol and through activating caspase-3 in human leukemia HL-60 cells in a concentration-dependent manner (3-50 μg/ml for cytochrome c and 10-50 μg/ml for caspase-3) [34]. The cell death induced by propolis was largely prevented by treating HL -60 cells with 30 μM z-DEVD-fmk, a caspase-3 inhibitor [23].…”
Section: The Effect Of Propolis On the Apoptotic Process In Cancer Cellssupporting
confidence: 76%
“…The mechanism of apoptosis induced by propolis seems dependent on the kind of compounds and the concentration of the propolis extract. Recent studies suggest that the astaxanthin and flavonoids in propolis can protect SH-SY5Y cells from beta-amyloid (A beta) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) induced apoptotic death [23].…”
Section: The Influence Of Propolis and Its Compounds On The Apoptoticmentioning
confidence: 99%
“…Scientists from Kyonggi University [30] in their research confirmed the proapoptotic effects of ethanol extract of propolis. They carried out an experiment whose purpose was to define DNA fragmentation that is considered to be one of the morphological symptoms of physiological cell death process.…”
Section: Discussionmentioning
confidence: 84%
“…It has been demonstrated that propolis and some of its active substances have anti carcinogenic and antitumor effect both in vitro and in vivo tumor models (40–43). Propolis and its phenolic compounds have been demonstrated to induce inhibition of growth and apoptotic cell death in human melanoma A2058 cells, human breast cancer MCF-7 cells, human neuroblastoma IMR-32 cells, rat glioma C6 cells, and human leukemia HL-60 cells (44), as well as human leukemia U937 cells (15) and four human colon carcinoma cell lines (45), among others.…”
Section: Discussionmentioning
confidence: 99%